Managers and employees perceived leadership behavior: expatriate and local bosses - Tangaya, Davendran (2010)

(untitled)
The purpose of this research is to investigate the manager and employees perceived leadership behavior of their expatriate and local bosses in terms of 12 subscales of leadership behavior.